Mobile number portability of Robi Axiata ltd.: acquiring more customers and sustain the existing market during the era of mobile number portability - Choudhury, Ananya (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.